2013
DOI: 10.1631/jzus.bqicc703
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rosuvastatin on the production and activation of matrix metalloproteinase-2 and migration of cultured rat vascular smooth muscle cells induced by homocysteine

Abstract: Abstract:Objective: To test the influence of homocysteine on the production and activation of matrix metalloproteinase-2 (MMP-2) and tissue inhibitors of matrix metalloproteinase-2 (TIMP-2) and on cell migration of cultured rat vascular smooth muscle cells (VSMCs). Also, to explore whether rosuvastatin can alter the abnormal secretion and activation of MMP-2 and TIMP-2 and migration of VSMCs induced by homocysteine. Methods: Rat VSMCs were incubated with different concentrations of homocysteine (50-5 000 μmol/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
1
9
0
1
Order By: Relevance
“…In the present study, it was found that Hcy (50–500 μmol/L for 6–24 h) induced VSMCs migration in a time and dose dependent manner. The results were consistent with data published previously . This study also showed that ROS are strongly involved in Hcy induced VSMCs migration, since radical scavengers NAC reduced VSMCs migration by 17.97%.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, it was found that Hcy (50–500 μmol/L for 6–24 h) induced VSMCs migration in a time and dose dependent manner. The results were consistent with data published previously . This study also showed that ROS are strongly involved in Hcy induced VSMCs migration, since radical scavengers NAC reduced VSMCs migration by 17.97%.…”
Section: Discussionsupporting
confidence: 93%
“…Derangement of MMP-2 expression and activity alters the balance between ECM synthesis and degradation, resulting in excessive collagen deposition and reduced structural integrity in the myocardium. Increasing degradation of ECM supplies space for the proliferation and migration of HCF and other macrophagocytes, which secrete inflammatory and growth factors, further enhancing the cardiac remodeling process (21). Siddesha et al (22), showed that sustained induction and activation of MMPs and the destruction and deposition of ECM can result in cardiac fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…18 MMPs and TIMPs together maintain the balance of ECM and participate in the regulation of VSMC migration and proliferation. 13 Oak et al 19 found that red wine polyphenols inhibited VSMC proliferation and migration mainly by decreasing the expression and activity of MMP-2. Recent studies further confirmed that resveratrol from red wine polyphenols could inhibit VSMC proliferation by suppressing ROS generation and inhibit VSMC migration by reducing MMPs expression.…”
Section: Discussionmentioning
confidence: 99%
“…The activated MMP-2 can also activate other signaling pathways such as p-AKT and p-ERK1/2 that could induce the migration and proliferation of VSMCs, 24,29,30 and the degradation of ECM supplies space for the migration and proliferation of VSMCs. 13 What is more, the activated VSMCs can then secrete and activate more MMP-2 and aggravate the imbalance of MMP-2/TIMP-2, resulting in the development and rupture of atherosclerotic plaques. 31 Our results showed that polyphenols and polypeptides in the Chinese rice wine could decrease the expression and activity of MMP-2 and MMP-9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation